SUSTANCIAS NO ILEGALES UTILIZADAS COMO DROGAS: “INCIENSO”, “SALES DE BAÑO” Y OTRAS. - Quesada Aguilar, Carlos I. (2012)
In the past few years, there has been a  raising concern about the spread use of chemical synthetic substances, non-illegal, which its apparent purpose is to be used as “incense” or “bath salts”, but in fact, their components are synthetic cannabinoids or stimulant drugs. Because its condition of non-illegal, they are sold over the counter and can be reached for any person. There are reports in the medical literature, mainly associated to mental disturbances and psychosis. It is imperative to know the presence of this kind of toxic substances, their clinical manifestations and treatment, as well as to motivate the authorities to generate the appropriate strategies to limit its use.